Status of yam (Dioscorea spp.) in the Democratic Republic of Congo - Adejumobi, I.I.; Agre, A.P.; Adeyinka, A.S.; Cipriano, I.M.; Adheka, J.G.; Onautshu, O.D. (Wiley, 2023)
Yam is an important tuber crop with enormous potential to enhance rural sustenance and livelihood in DRC. However, studies to enhance its genetic improvement are very far from sufficient with only a handful of information available on the crop. Yam has been treated as an orphan crop compared to contemporary crops such as cassava and sweet potato which have adapted to different cropping systems and become widespread in production. The lack of research attention to address the major production challenges has further decreased the value and potential of the crop compared to its contemporaries. These production constraints include lack of adequate quality planting materials, low yield potential, poor resistance/tolerance to yam mosaic and anthracnose diseases and ultimately poor tuber quality attributes focusing on tuber taste, flesh oxidation and dry matter contents of the majority of the farmers preferred varieties. In this review, we evaluated the status of yam in DRC and presented the needful activities to be incorporated for its improvement. Diversity has however been maintained mainly through ennoblement efforts in house gardens and small farmlands using traditional farming methods. Studies from other nations where yam has been successful with prominence in characterization and genetic improvement brought to light the need for DRC to consider yam as a staple carbohydrate food source, even to the extent of modifications in food public policy. Reversal of the yam's current stigma is a challenge to the scientific community and the population in general.